Good Corporate Governance, Capital Structure, and Earnings Management: Moderating Sustainability Reporting in Energy Issuers (E-Jurnal Akuntansi, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) mechanisms, as indicated by the board of directors, audit committee, independent board of commissioners, managerial ownership, and capital structure, on earnings management in energy sector companies listed on the Indonesia Stock Exchange for the period 2021-2024. This study also examines the moderating role of sustainability reporting, measured using the GRI disclosure index, in this relationship.This study uses a quantitative approach with purposive sampling of 22 energy sector companies, resulting in 88 observations. Earnings management is measured using the Modified Jones Model, while sustainability reporting is measured based on the completeness of disclosure of the GRI Universal Standards 2021 and energy sector-specific standards. Data analysis used multiple linear regression and Moderated Regression Analysis (MRA).The results show that only managerial ownership has a significant negative effect on earnings management, while the board of directors, audit committee, independent board of commissioners, and capital structure have no significant effect. The audit committee even shows a significant positive effect on earnings management. As a moderating variable, sustainability reporting was found to strengthen the supervisory function of the audit committee and weaken the positive influence of capital structure on earnings management, but it weakened the effectiveness of the board of directors and independent commissioners. These findings indicate the phenomenon of ceremonial adoption in the implementation of GCG and sustainability reporting in the Indonesian energy sector, where the formal governance structure does not yet reflect a substantive supervisory function
Keywords: Earning Management; Good Corporate Governance; Capital Structure; Sustainability Reporting; GRI Disclosure Index